The Effectiveness of Homemade Soymilk in Increasing Haemoglobin (Hb) Levels in Pregnant Women - Teungku Nih Farisni; Fitriani Fitriani; Yarmaliza Yarmaliza (Universitas Teuku Umar, 2019)
The high prevalence of anaemia in pregnant women in West Aceh Regency (40.5%), which is indicated by the haemoglobin (Hb) levels of below 11 g%, should receive special attention because anaemia will have an impact on maternal and infant mortality. Soy milk is one processed beverage that contains iron, high protein, essential fatty acids, fibre, vitamins and minerals. Nutrients contained in soy can produce energy, maintain optimal body functions, and meet the needs of iron in pregnant women. Soybean is a type of food which is ranked third to have the richest iron (8.8 mg%) after meat and cereals. The purpose of this study was to examine the effectiveness of homemade soy milk in increasing Hb levels in pregnant women. The study design was an experiment on pregnant women. The object of this study was pregnant women in their first and second trimester of pregnancy. The intervention was giving homemade soy milk by adding 10 ml of honey, as a substitute for sugar, to 1 cup of homemade soy milk (250 ml), from a basic intake of 4 mg of iron per day for pregnant women. This intervention resulted in a significant increase in Hb levels in pregnant women (P < 0.005). The provision of homemade soy milk can significantly increase the mean of Hb levels in pregnant women with an average increase of 2.99 mg% ± 1.422. Furthermore, the p-value obtained was = 0.000, indicating that there was a significant difference in Hb levels between measurement I (before being given homemade soy milk) and after being given homemade soy milk for 3 months. Homemade soy milk is an effective drink in increasing Hb levels in pregnant women.